Language, solidarity, and identity: The role of jargon in the League of Legends community - Abdulhasib Hasan Al Banna; Nur Utami Sari'at Kurniati; Jordy Satria Widodo (Journal Albion : Journal of English Literature, Language, and Culture, 2025)
This study aims to identify and analyze the various forms and meanings of jargon used within the League of Legends community. The research employs Yule’s (2017) theory of jargon and Gaikwad and Kuchekar’s (2022) framework for word class classification, utilizing a descriptive qualitative approach. Data were collected from the official mic check video of the 2024 LEC finals, which captured direct communication between players and commentators throughout the matches. The findings reveal 51 instances of jargon, comprising 35 nouns, 14 verbs, 1 adjective, and 1 adverb. The analysis demonstrates that while nouns and verbs are the most prevalent, other word classes play a significant role in conveying more nuanced and contextually relevant meanings. In this community, jargon not only serves as a means of communication but also helps to reinforce solidarity and identity among players in a competitive and digital gaming environment.